RF design and tuning of a deuteron RFQ for detecting impurity deposition on a tokamak. (24th January 2022) - Liu, S.; Bai, Q.; Wei, Y.X.; Lu, Y.R.; Wang, Z.; Han, M.Y.; Li, H.P.; Tan, Q.Y.; Wei, T.H.; Xia, Y.; Zheng, P.F.
Abstract: Peking University and Southwestern Institute of Physics are jointly developing a new deuteron Radio Frequency Quadrupole (RFQ) accelerator to study the migration and deposition of impurities on the first wall of a tokamak facility. The RFQ operates at 162.5 MHz with the duty factor of 1%, which can accelerate 10 mA deuteron beam from 40 keV up to 1.5 MeV within 2.2 m length. Such four-vane RFQ is divided into two segments and equipped with 40 tuners in total. In the electromagnetic (EM) design, the dipole stabilizer rods (DSRs) were optimized to obtain a mode separation of 3.1 MHz. The tuners and undercuts were also designed and optimized to fulfill the requirements of the resonant frequency, flat longitudinal field distribution and field tuning. Following the EM design, multi-physics analysis and structure error analysis was carried out. The cavity was fabricated with 99.9% oxygen-free electronic (OFE) copper. The assembly and braze of each RFQ module have been completed, the results of metrological measurements via coordinate measuring machine (CMM) indicate that there was no unexpected deformation. The intrinsic Q-value of the whole cavity is 12834 in the low level radio frequency (RF) measurements, which is 87% of the theoretical simulation with electrical conductivity of 5.8 × 10 7 S/m. After tuning, the quadrupole perturbative component decreased from 2.6% to 0.6%, and the dipole perturbative components decreased from 6.1% to 1%.